2009
DOI: 10.1017/s0022112009007964
|View full text |Cite
|
Sign up to set email alerts
|

Vortex wakes of a flapping foil

Abstract: We present an experimental study of a symmetric foil performing pitching oscillations in a vertically flowing soap film. By varying the frequency and amplitude of the oscillation we visualize a variety of wakes with up to 16 vortices per oscillation period, including von Kármán vortex street, inverted von Kármán vortex street, 2P wake, 2P+2S wake and novel wakes ranging from 4P to 8P. We map out the wake types in a phase diagram spanned by the width-based Strouhal number and the dimensionless amplitude. We fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
191
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(224 citation statements)
references
References 27 publications
32
191
1
Order By: Relevance
“…Schnipper, Andersen & Bohr (2009) obtained a rich variety of these vortex wakes by varying the amplitude and frequency of the oscillation, with most of them showing strong downstream persistence. We therefore expect regular pattern of vortices to be convectively unstable in a wide range of configurations.…”
Section: Discussionmentioning
confidence: 99%
“…Schnipper, Andersen & Bohr (2009) obtained a rich variety of these vortex wakes by varying the amplitude and frequency of the oscillation, with most of them showing strong downstream persistence. We therefore expect regular pattern of vortices to be convectively unstable in a wide range of configurations.…”
Section: Discussionmentioning
confidence: 99%
“…These predictions do not prescribe some sort of '1 motion-1 vortex' model. For fluttering filaments and actuated airfoils, it has been clearly shown that there need not be a 1:1 relationship between shed vortices and the structure's oscillatory motion (Lentink et al, 2010;Schnipper et al, 2009;Zhang et al, 2000;and references therein). We suggest that aerodynamic excitation of a feather causes it to flutter when aerodynamic energy received exceeds structural damping, and that periodicity is set in part by the structural resonance of the feather.…”
Section: Discussionmentioning
confidence: 99%
“…15. For a clear definition of wake trend, we shall use "S" to denote a single vortex and "P" to denote a pair of vortices of opposite signs [25]. Accordingly, in …”
Section: A Shape Optimization For a Symmetric Airfoil (Naca 0012)mentioning
confidence: 99%